Safety Assessment of Zigbir®: A Polyherbal Formulation in Sprague-Dawley Rats - Joseph Joshua Allan; Ranjit Madhukar Bhide; Amit Agarwal (Journal of Toxicology)
The safety of Zigbir®, a polyherbal formulation intended for use as food supplement, was evaluated in Sprague-Dawley rats treated orally at the dose of 2000 mg/kg in acute and at 250, 500, and 1000 mg/kg for 90 days in subchronic toxicity study. The median lethal dose of Zigbir® was found to be more than 2000 mg/kg, and fourteen-day repeated dose toxicity study revealed it to be safe up to 1000 mg/kg. The subchronic study did not show any mortality or treatment-related adverse clinical signs. The treated animals exhibited normal feed intake and comparable body weight gain except for a decrease in females of 500 and 1000 mg/kg groups. Ocular examination revealed no abnormalities. Further, Zigbir® administration in rats did not induce any major changes in urinalysis, hematological, and biochemical evaluations except for minor alterations in few parameters at different dose levels. Gross and histopathological findings did not show any lesions attributable to Zigbir® administration. The no observed effect level of Zigbir® was found to be 500 and 250 mg/kg in male and female Sprague-Dawley rats.